1990
DOI: 10.1139/y90-209
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of myometrial desensitization to β-adrenergic agonists

Abstract: Continuous exposure of ovine myometrial strips exposed to isoproterenol (10 microM) resulted in only transient inhibition with contractions returning within 60 min. Rechallenging these strips with isoproterenol failed to induce inhibition, confirming the occurrence of desensitization. In contrast, exposure of myometrial tissue to isoproterenol for only 5 min did not result in desensitization. Myometrial strips exposed to isoproterenol demonstrated a significant increase in cAMP content associated with inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In contrast, we found that de sensitization was associated with a significant re duction in the number (but not affinity) of β-adren ergic receptors. 41 We have observed similar examples of homolo gous myometrial desensitization to β-adrenergic agonists in vivo in rats 43 as well as nonpregnant 44 and pregnant sheep. 45 In the latter study preterm labor was induced in sheep by injection of the pro gesterone receptor antagonist, RU486.…”
Section: Homologous Desensitizationsupporting
confidence: 54%
See 1 more Smart Citation
“…In contrast, we found that de sensitization was associated with a significant re duction in the number (but not affinity) of β-adren ergic receptors. 41 We have observed similar examples of homolo gous myometrial desensitization to β-adrenergic agonists in vivo in rats 43 as well as nonpregnant 44 and pregnant sheep. 45 In the latter study preterm labor was induced in sheep by injection of the pro gesterone receptor antagonist, RU486.…”
Section: Homologous Desensitizationsupporting
confidence: 54%
“…Administration of β-agonists in vitro produces only a transient inhibi tion of contractile activity with contractions return ing even though the myometrium remains exposed to active drug. 22,41,42 Coincident with this loss of responsiveness is a significant reduction in tissue cAMP levels and in β-agonist induced cAMP accu mulation. Postreceptor mechanisms remained func tional during homologous desensitization of the myometrium because elevation of endogenous cAMP levels by methods that bypass the β-receptor (e.g., inhibition of cAMP-dependent phosphodiesterase activity, direct activation of adenylyl cyclase, or ad dition of GTP analogues) induces a rapid and sig nificant inhibition of myometrial contractile activity in desensitized tissue.…”
Section: Homologous Desensitizationmentioning
confidence: 99%
“…Mechanisms for such a desensitizing phenomenon at the level of receptors have recently been reported to be similar to that of ƒÀ-adrenergic receptors (ƒÀ-ARs) (Mahan et al, 1985;Dayes et al, 1990;Hausdorff et al, 1990 A reported experiment using uterine muscle strips revealed that OT-induced uterine contraction tended to become weaker 30-60 minutes after OT treatment (Eiler et al, 1989). In the present study, however, the total OTR concentration showed no change during the 30 minute period after the addition of OT.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenergic β ‐agonists have been used for the management of preterm labor, as they are effective in suppressing uterine smooth muscle contraction. However, it has been argued that β ‐agonists are not always beneficial for the treatment of preterm labor because there is a downregulation of β ‐adrenergic receptors and/or an uncoupling of β ‐adrenergic receptor to adenylate cyclase via Gs in the patients ( Litime et al , 1989 ; Dayes & Lye, 1990). The present study in human materials suggests that the inhibition of PKC β may be a novel therapeutic strategy in the treatment of the preterm labor.…”
Section: Discussionmentioning
confidence: 99%